Probiotic Supplementation in Poultry Production as an Alternative to Antibiotic Feed Additive - Birmani, Muhammad Waseem; Nawab, Aamir; Ghani, Muhammad Waseem; Li, Guanghui; Wu, Jiang; Liu, Wenchao; An, Lilong (Animal Review, 2019)
Provision of safe and healthy poultry products to the human being is the prime objective of the poultry industry, but one should keep in mind the welfare of animals and reverence for the environment. Meat and eggs demand also increasing with the increase in world human population. To meet this increasing demand for meat and eggs, antibiotics growth promoters were used world widely. After the ban on antibiotics growth promoters due to its residual effects on human health, nutritionists are focusing on novel growth promoters those without causing productivity loss, or product quality has augmented. Therefore, probiotics are a safe alternative to antibiotics and its beneficial effects proven from many decades. Live microorganisms are used to deliver health benefits to chicken, usually by reestablishing or improving the intestinal microbiota. Probiotics have a beneficial effect on weight gain, immunity, meat traits and somewhat impact on gut health of poultry. The subject of review paper will be worthwhile meant for researchers and poultry nutritionists to advance their understanding of alternatives to antibiotics in poultry production without affecting performance and the welfare of chicken.